Capillary-driven spontaneous oil/water separation by superwettable twines. Issue 31 (17th July 2015) - Xu, Li-Ping; Dai, Bing; Fan, Junbing; Wen, Yongqiang; Zhang, Xueji; Wang, Shutao
Abstract : Efficient absorption and self-removal of oil and water by superwettable twines. Abstract : A superwettable twine showing excellent absorption and self-removal capacity of oil and water from oil/water mixtures is reported. Superwettable materials are fabricated by simple modification of commercial twines with plasma and hydrophobic silica nanoparticles, respectively. We show that the absorption and self-transportation of oil and water are driven by the capillary force resulting from the microgaps and microgrooves on twines.